Notary and the Implementation of Integrated Electronics Business Licensing Services - RIVIYUSNITA, Rianda; JAUHARIAH, Jauhariah; BUSROH, Firman Freaddy (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
Since the enactment of Government Regulation Number 24/2018 concerning Electronic Integrated Licensing Services, every licensing service activity must go through the Online Single Submission (OSS) system. The purpose of this regulation is to simplify the service of copying. With the enactment of these regulations, it also influences the duties and roles of the notary to help business actors. Along with the Industrial Revolution era, Notaries must also be able to adapt and use the system. In reality, some problems were found so that it hampered the licensing services assigned to the Notary. For this reason, coordination with related parties is needed so that the system runs well.